Recycling of mixed cathode lithium‐ion batteries for electric vehicles: Current status and future outlook. Issue 1 (10th January 2020) - Or, Tyler; Gourley, Storm W. D.; Kaliyappan, Karthikeyan; Yu, Aiping; Chen, Zhongwei
Abstract: Worldwide trends in mobile electrification, largely driven by the popularity of electric vehicles (EVs) will skyrocket demands for lithium‐ion battery (LIB) production. As such, up to four million metric tons of LIB waste from EV battery packs could be generated from 2015 to 2040. LIB recycling directly addresses concerns over long‐term economic strains due to the uneven geographic distribution of resources (especially for Co and Li) and environmental issues associated with both landfilling and raw material extraction. However, LIB recycling infrastructure has not been widely adopted, and current facilities are mostly focused on Co recovery for economic gains. This incentive will decline due to shifting market trends from LiCoO2 toward cobalt‐deficient and mixed‐metal cathodes (eg, LiNi1/3 Mn1/3 Co1/3 O2 ). Thus, this review covers recycling strategies to recover metals in mixed‐metal LIB cathodes and comingled scrap comprising different chemistries. As such, hydrometallurgical processes can meet this criterion, while also requiring a low environmental footprint and energy consumption compared to pyrometallurgy. Following pretreatment to separate the cathode from other battery components, the active material is dissolved entirely by reductive acid leaching. A complex leachate is generated, comprising cathode metals (Li +, Ni 2+, Mn 2+, and Co 2+ ) and impurities (Fe 3+, Al 3+, and Cu 2+ ) from the current collectors and battery casing, which can be separated and purified using a series of selective precipitation and/or solvent extraction steps. Alternatively, the cathode can be resynthesized directly from the leachate. Abstract : This work reviews lithium‐ion battery recycling developments in the literature in the context of meeting demands for the growing electric vehicle (EV) market. Practical challenges associated with the collection and disassembly of EV battery packs are also discussed. With respect to metal recovery, a particular emphasis is placed on hydrometallurgical processes, as it is robust in handling various metal compositions.